Global Fund: Making Uganda’s CCM Work Through Full Engagement of Civil Society - HEPS (HEPS, 2008)
HIV/AIDS have over the recent years been receiving increasing funding, especially from the donor community. However, due to the absence of a mechanism to monitor and aggregate the contributions from the wide range of funders, the exact amount of funding coming from foreign donors, non-governmental organisations, individuals and even the Uganda government itself, is not known. Independent attempts to determine the actual level of funding have been hampered by the Ministry of Health’s failure to harmonize the various funding structures of the different funders, the multi-sectoral nature of the response, reluctance by the donors to provide complete information about their budgets and expenditure, and difficulty in capturing household contributions towards HIV/AIDS care. There is therefore, a gap that needs to be filled by regular tracking of HIV/AIDS funding, to establish the actual level of funding and the extent to which it reaches the intended beneficiaries. Even with the limited information available, it is obvious that funding for HIV/AIDS is still insufficient, given that access to HIV/AIDS services – from counseling and testing (HCT) to anti-retroviral therapy (ART) and care and support – remains limited. The health care system is urgently in need of additional resources, particularly to accommodate the burden of the HIV/AIDS epidemic. The public sector needs not only to increase its per capita health expenditure to US$28 – and up to US$40 when anti-retroviral drugs (ARVs) are included – to enable its citizens realise their right to health, but also to make the available work for the poor.